Bots and Automation over Twitter during the Second U.S. Presidential Debate - Howard, P; Kollanyi, B; Woolley, S (Political Bots, 2016)
Bots are social media accounts that automate interaction with other users, and political bots have been particularly active on public policy issues, political crises, and elections. We collected data on bot activity using the major hashtags related to the U.S. Presidential debate. In this brief analysis we find that (1) Twitter traffic on pro-Trump hashtags was roughly double that of the pro-Clinton hashtags, (2) about one third of the pro-Trump twitter traffic was driven by bots and highly automated accounts, compared to one quarter of the pro-Clinton twitter traffic, (3) the significant rise of Twitter traffic around debate time is mostly from real users who generate original tweets using the more neutral hashtags. In short, Twitter is much more actively pro-Trump than pro-Clinton and more of the pro-Trump twitter traffic is driven by bots, but a significant number of (human) users still use Twitter for relatively neutral political expression in critical moments.